Moral issues in sport: The child's perspective - Stuart, M. E. (Research Quarterly for Exercise and Sport, 2003)
Sport offers opportunities for children to identify and resolve moral issues. Moral issues in sport have primarily been studied from the researcher`s perspective, with the child`s perspective relatively ignored. Thus, the purpose of this study was to explore the nature and content of the issues children experienced in sport. Interview participants consisted of 7 boys and 8 girls ranging in age from 10 to 12 years (M = 11.6 years, SD = 1.7) who had competitive youth sport experience. An inductive content analysis revealed that children identified issues surrounding three overall dimensions concerning fairness of adult`s actions, negative game behaviors, and negative team behaviors. Specific examples of issues included unfair actions by coaches, disrespecting opponents, and selfish behavior in practice. The self-identified issues both confirmed and expanded upon the content found in hypothetical moral dilemmas in sport.